SIKAP KEAGAMAAN MAHASISWA DI DAERAH ISTIMEWA YOGYAKARTA - Mami Hajaroh (Jurnal Kependidikan, 1999)
Abstract The purposes of this study were to describe college students’ religious attitudes and the effect of family education, campus environment, and students’ religious knowledge on their religious attitudes. The population of this study was all college categories with a sample of 382 students. The multi stage random sampling was used for the sampling. The data were collected using a pretested questionnaire. The factor analysis is used for testing the instrument validity, and Alpha Cronbath analysis is used for reliability. The data analysis was performed using a descriptive statistical technique and analysis of regression. The descriptive analysis result shows that students’ religious attitudes were in the medium category. There is a positive effect of family education, campus environment, and religious knowledge on the religious attitudes. The largest effect is of religious knowledge, and then followed by family education, and the smallest effect was that of campus environment. Keywords: religious attitude; college student